3(x – 6) = -15 + 3x Yes no solution show work

Question

3(x – 6) = -15 + 3x

Yes no solution show work

in progress 0
Ngọc Hoa 2 days 2021-07-21T23:12:21+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-21T23:13:42+00:00

    Answer:

    see explanation

    Step-by-step explanation:

    Given

    3(x – 6) = – 15 + 3x ← distribute parenthesis on left side

    3x – 18 = – 15 + 3x ( add 18 to both sides )

    3x = 3 + 3x ( subtract 3x from both sides )

    0 = 3 ← not possible

    This indicates the equation has no solution

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )